Occurrence, sustainable treatment technologies, potential sources, and future prospects of emerging pollutants in aquatic environments: a review - Zhou, Qiqi; Chen, Hongfeng; Liu, Guijian; Wang, Xiaohui (Frontiers in Environmental Science, 2024)
Emerging contaminants (ECs), such as polyfluorinated compounds, antibiotics, microplastics, and nonylphenol, continue to challenge environmental management practices due to their persistence and bioaccumulation potential. This review articulates the critical pathways and environmental risks posed by these contaminants, setting the stage for an in-depth exploration of innovative removal technologies. We spotlight groundbreaking methods that are reshaping the landscape of ECs remediation: membrane filtration technology, constructed wetlands, adsorptive materials, algae-based systems, biological treatments, and advanced oxidation processes. Each method is evaluated for its efficacy in removing ECs, with particular emphasis on sustainability and economic viability. Our findings reveal that integrating these technologies can significantly enhance removal efficiency, offering new directions for environmental policy and practical applications. This article positions these advanced removal technologies at the forefront of the fight against ECs, advocating for their broader adoption to safeguard environmental and public health.